ANALISIS FAKTOR PRIORITAS PRODUKSI PANGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DI KABUPATEN KUTAI KARTANEGARA - Rizky Arif Nugroho; Muhamad Dickiaulia; Mohtana Karisma Kadri (Jurnal Penelitian Pertanian Terapan, 2020)
Food security is a strategic issue in every country. In the fourth phase of the National Medium-Term Development Plant (RPJM), food security is one of the focuses of the development. East Kalimantan is one of the provinces experiencing food shortages. The intensity of food shortages reaches 90,000 tons per year. The number of food shortages reaches 26% of the total food needs in East Kalimantan. Kutai Kartanegara Regency is a location designated as the rice barn of East Kalimantan, but Kutai Kartanegara Regency has not been able to fulfill its food needs independently. Therefore, research is needed to be related to the factors that influence food production in Kutai Kartanegara Regency. The variables used in this study were 22 variables. The analysis technique used is the Analytical Hierarchy Process (AHP) using a sample of 100 farmers and breeders in Kutai Kartanegara Regency. The results of the analysis phase that have been carried out are obtained in the priority order of the variables studied. The top three variables that become the main priority are agricultural capital, livestock capital, and plantation capital.